(untitled) (Philological Studies, 2019)
Wojciech Kuczok in his novel Gnoj portrays a new image of a family, which is dominated by twisted interpersonal relationship, the most clearly exspressed by violence of the father towards his son. Kuczok uses inovative composition and thoughtful process of the genre of family saga and the use of style of reportage to represent narrator, trapped in the trauma of his childhood. Intimate story presents a different point of view towards Polish society and its atributes.